Correlation between reflectance and refractive index of different liquids using an optical time domain reflectometer (OTDR) - Hashim, Sapull Nizam (2013)
Recently, the area of measurement and instrumentation and particularly sensor development has undergone fast development. Among the active advancement of sensor based microelectronics development, the optical based sensor has expanded promisingly over these past years due to its key advantages such as compact size, low power consumption, corrosion and electrical spark free which would cause a fire in the explosive environment, electromagnetic interference proof, high sensitivity and large distance between signal detection that is possibility of enabling a long distance measurements. For instance, refractive index sensors have attracted considerable attention in biological and chemical applications. Thus many optical sensors for refractive index (RI) detection have been proposed. Therefore, this research was carried out in order to seek the correlation between reflectance and refractive index of different liquids using an optical time domain reflectometer (OTDR) via single mode fibre (SMF) of 100m length. There are three objectives that are to observe the fluctuation in the fiber end of the five liquids (water, acetic acid, 1-butanol, 1-octyne and ethyl glycol with their corresponding RI are 1.33, 1.337, 1.40, 1.42 and 1.43), to clarify experimentally the correlation between reflectance with RI of the liquids and to analyze the potential of using the OTDR technique for measurement RI of liquids. Each liquid is measured 10 times in order to obtain good average value of reflectance reading under three different pulse widths (20ns, 50ns and 100ns). After completing the data analysis, the fluctuations in reflection readings of the liquids is within 6%. The experimental and simulation curves are similar in trend and the OTDR technique has the potential in measuring RIs of liquids.